Assessing indicators for selection of participants for the Vulnerable Group Development (VGD) program in Bangladesh - Ahmed, Akhter (International Food Policy Research Institute, 2018)
Bangladesh has a wealth of institutional diversity and experience with targeted social safety net programs. Most of these programs are widely credited with providing the poor access to food and improving their livelihoods. However, the need for assistance is overwhelming. According to the latest poverty estimates, 24.3 percent of the country’s 163 million people were poor in 2016.1 Improving program targeting to reach the poorest of the poor effectively is needed to address the wide gap between the resources available for safety net programs and those in need of support. Targeting effectiveness indicates the extent to which program benefits are received by the neediest versus the less needy or non-needy population. A well-targeted food intervention improves the real income and food security of the neediest without providing those benefits to members of the society who do not need them. Targeting of benefits to those most in need is an obvious way of reducing the costs of a program. Upon request of the Ministry of Women and Children Affairs (MOWCA) and the World Food Programme (WFP) in Bangladesh, the International Food Policy Research Institute (IFPRI) has undertaken this study to assess the suitability of indicators used for targeting the poor through the Vulnerable Group Development (VGD) program in Bangladesh. The VGD program is the largest social safety net program in Bangladesh that exclusively targets women. About 750,000 ultra-poor rural women and their 3.75 million family members receive a monthly ration of 30 kg of rice for 24 months. This support period is referred to as the “VGD cycle.” The program began in 1975 as a relief program for families affected by natural calamities. The current VGD program seeks to integrate food security and nutrition with development and income generation. The program is implemented by the MOWCA with support from the WFP.